GE_GERICHTE P/21210/2018 vom 8. Juli 2021 - GE Cour de justice (2021)
CLASSEMENT DE LA PROCÉDURE;OPPORTUNITÉ;CAS BÉNIN;PRÉSOMPTION D'INNOCENCE;FRAIS DE LA PROCÉDURE | CPP.319; CEDH.6; CPP.10; CP.52; CPP.426.al2